2020
DOI: 10.1515/cclm-2020-0300
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of stool DNA preparation protocols for colorectal cancer screening via analysis of DNA methylation biomarkers

Abstract: ObjectivesColorectal cancer (CRC) screening using stool samples is now in routine use where tumor DNA methylation analysis for leading markers such as NDRG4 and SDC2 is an integral part of the test. However, processing stool samples for reproducible and efficient extraction of human genomic DNA remains a bottleneck for further research into better biomarkers and assays.MethodsWe systematically evaluated several factors involved in the processing of stool samples and extraction of DNA. These factors include: st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Currently, non-coding RNA, circulating exosome factors and cerebrospinal fluid can be the scope of seeking glioma biomarkers [7, 34, 3638]. However, this study suggests that in addition to circulatory source factor expression differences and prognostic analysis, systematic analysis and evaluation based on markers are also key to validate their reliability [39, 40], such as assessing the intrinsic and extrinsic association and risk of marker genes, which are also needed. Therefore, a relatively typical marker - UBE2C was selected based on systemic intrinsic factors such as differential expression genes, risk genes, cell cycle and DNA replication in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, non-coding RNA, circulating exosome factors and cerebrospinal fluid can be the scope of seeking glioma biomarkers [7, 34, 3638]. However, this study suggests that in addition to circulatory source factor expression differences and prognostic analysis, systematic analysis and evaluation based on markers are also key to validate their reliability [39, 40], such as assessing the intrinsic and extrinsic association and risk of marker genes, which are also needed. Therefore, a relatively typical marker - UBE2C was selected based on systemic intrinsic factors such as differential expression genes, risk genes, cell cycle and DNA replication in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, non-coding RNA, circulating exosome factors and cerebrospinal uid can be the scope of seeking glioma biomarkers [7,34,[36][37][38]. However, this study suggests that in addition to circulatory source factor expression differences and prognostic analysis, systematic analysis and evaluation based on markers are also key to validate their reliability [39,40], such as assessing the intrinsic and extrinsic association and risk of marker genes, which are also needed. Therefore, a relatively typical marker -UBE2C was selected based on systemic intrinsic factors such as differential expression genes, risk genes, cell cycle and DNA replication in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar report performed a methylation analysis using MethyLight qPCR and droplet digital PCR, reporting elevated CpG islands methylation in two genes: GRIA4 and VIPR2 [60]. Two additional DNA methylation markers analysed with multiplex quantitative PCR assay, SDC2 and NDRG4, were found in another study, providing a solid foundation for multi-target DNA biomarker analysis in stool samples for CRC screening [61]. Previously, other authors reported SDC2 methylation as a good candidate for potential non-invasive diagnostic tool for early detection of CRC [62].…”
Section: Genomicsmentioning
confidence: 91%